P-P36 AXIOS™ stents in the management of pancreatic fluid collections: case series from a single healthcare trust. (16th December 2021) - Doyle, Joseph; Latip, Nadiah; McCain, Stephen; Scott, Ryan; Love, Mark; Taylor, Mark; Vass, David; Jones, Claire; Kirk, Gareth; McKie, Lloyd; Diamond, Thomas
Abstract: Background: This was a consecutive case-series of all pancreatic fluid collections (PFCs) managed with AXIOS™ stents in a 3 year period from a single healthcare trust, retrospectively analysed to determine the rate of technical success, clinical success and adverse events related to the procedure. Methods: All patients in who underwent AXIOS stenting for PFCs in the Belfast Health and Social Care Trust between May 2016 and July 2019 were included, with a follow-up period of 1 year. Electronic care records (ECR) and Radiology reports were reviewed for each patient. PFCs were categorised into walled-of pancreatic necrosis (WOPN) and pseudocysts as per the revised Atlanta classification. The number of repeat procedures, endoscopic lavage +/- necrosectomy, the need for definitive surgery or any adverse events post-procedure were recorded. Results: 45 patients were included in the study (21 male, 24 female). 17 patients (37.8 %) had WOPN and 28 (62.2 %) pancreatic pseudocysts. Median collection diameter on CT imaging was 12 cm (range 6.2 – 22 cm). The procedure was technically successful in 43 patients (95.6%), with stent mal-deployment in the remaining 2. Median duration for stenting was 29.5 days (Range 13 – 92). The procedure was clinically successful for 33 patients (73.3%). n = 8 (17.8%) of patients were re-admitted with sepsis following stent insertion requiring intravenous antibiotics. n = 16 (35.6%) patients required repeated endoscopic lavage +/- necrosectomy following stent blockage (n = 11 WOPN, n = 5 pseudocyst). n = 2 (4.4%) stents accidentally dislodged during lavage necessitating surgical removal. n = 4 (8.9%) patients required a second AXIOS stent within 45 days of removal, n = 2 (4.4%) required CT guided drainage and n = 8 (17.8%) ultimately required surgical intervention.The rate of adverse events post-procedure was 33.3%. Conclusions: AXIOS stenting appears to be effective first-line in the "step-up" approach to managing PFCs. Despite some drawbacks, our study showed they were technically successful in 95.6% and clinically successful in 73.3% of cases, requiring no further intervention. For PFCs that do require surgery, AXIOS stenting may allow for a period of patient optimisation prior to definitive treatment.